Risk in the activity of an enterprise - Przemysław Łagodzki; Michał Kiełsznia (Journal of Agribusiness and Rural Development, 2011)
The phenomenon of the market competitiveness increase forces enterprises to consciously undertake a risk in order to guarantee themselves market safety and existence. It is dependent upon many factors both internal and external. The paper presents both the risk motion, kinds and sources. Additionally, the necessity of risk management in enterprises, as well as the stages of the process of management are discussed.